Nordic Noir from Within and Beyond - Hansen Kim Toft (Nordicom Review)
In this article, I show how a vision for the Nordic region exists as a banal Nordism, based on years of content exchange, Nordic co-production models, and public funding opportunities. I document how new commercial players have been able to gain a very large market share in only a few years, significantly disrupting the reach of public service broadcasters in the Nordic region. The three largest contemporary commercial players on the Nordic market – Viaplay, HBO, and Netflix – have been able to, in very different ways, tap into the ideology of banal Nordism and the geopolitical unity of the Nordic region, and they have done so by producing and acquiring content that has deep associations with one of the Nordic region's main international brands: Scandinavian crime fiction and Nordic Noir.